2023
DOI: 10.3390/v15020390
|View full text |Cite
|
Sign up to set email alerts
|

Antiviral Effect of Manganese against Foot-and-Mouth Disease Virus Both in PK15 Cells and Mice

Abstract: Foot-and-mouth disease (FMD) is an acute contagious disease of cloven-hoofed animals such as cattle, pigs, and sheep. Current emergency FMD vaccines are of limited use for early protection because their protective effect starts 7 days after vaccination. Therefore, antiviral drugs or additives are used to rapidly stop the spread of the virus during FMD outbreaks. Manganese (Mn2+) was recently found to be an important substance necessary for the host to protect against DNA viruses. However, its antiviral effect … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…A recent study demonstrated that the combined regimen of Mn 2+ and anti-PD-1 antibody showed promising efficacy, exhibiting type I IFN induction, manageable safety and revived responses to immunotherapy in most patients with tumors [11]. Our recent study showed that Mn 2+ can be highly effective in protecting C57BL/6N mice from being infected with FMDV [9], indicating that Mn 2+ is an effective antiviral additive for controlling viral infection in vivo. Therefore, it would be beneficial to carry out further study to explore their therapeutic potential against viral infection.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…A recent study demonstrated that the combined regimen of Mn 2+ and anti-PD-1 antibody showed promising efficacy, exhibiting type I IFN induction, manageable safety and revived responses to immunotherapy in most patients with tumors [11]. Our recent study showed that Mn 2+ can be highly effective in protecting C57BL/6N mice from being infected with FMDV [9], indicating that Mn 2+ is an effective antiviral additive for controlling viral infection in vivo. Therefore, it would be beneficial to carry out further study to explore their therapeutic potential against viral infection.…”
Section: Discussionmentioning
confidence: 84%
“…There's a study that demonstrated that Mn 2+ can promote STING activity by enhancing the binding affinity of 2 , 3 -cyclic guanosine monophosphateadenosine monophosphate (cGAMP) to STING and then induce the potent immunity against DNA viruses [8]. In addition, it was reported that Mn 2+ can also induce the immune response against the infection with RNA viruses, including Newcastle disease virus (NDV), foot-and-mouth disease virus (FMDV) and Sendai virus (SeV) [8][9][10]. A recent study discovered that Mn 2+ is also essential in the innate immune sensing of tumors via cGAS-STING [11].…”
Section: Introductionmentioning
confidence: 99%
“…The currently approved chemically inactivated whole virus FMD vaccine ( Doel, 2003 ), and an adenoviral vectored subunit FMD vaccine (Ad5-FMDV) approved for emergency use in the United States ( Grubman et al, 2010 ; Moraes et al, 2011 ), take at least 7 days to confer protection to vaccinated animals, during which time they are still susceptible to infection. There is a significant focus on developing biotherapeutics ( Medina et al, 2020b ; Kim et al, 2022 ) or antiviral agents ( Li et al, 2019 ; Mei-Jiao et al, 2019 ; Naeem et al, 2021 ; Zhang et al, 2023 ) to prevent the occurrence of FMDV infections during the vulnerable period prior to vaccine-induced humoral immunity, thereby closing this window of susceptibility.…”
Section: Introductionmentioning
confidence: 99%